Corporate Criminal Liability as a Catalyst for Effective Anti-corruption War in Nigeria - Akanbi, Khairat Oluwakemi (NIU Journal of Humanities, 2018)
One of the focal point of campaign in the build up to the presidential elections in 2015 was the promise of anti-corruption fight.  This is because corruption has been one of the challenges of Nigeria’s development as the country has been persistently listed as being among corrupt countries in the world.  According to former President Olusegun Obasanjo, corruption is a cankerworm that has eaten deep into the fabric of the Nigerian society.  Usually, in cases of corruption which has to do with bribery especially when large capital is involved, corporations are usually involved either as offeror of bribe, facilitator of bribe or are used to syphon funds illegally acquired through corrupt activities.   A cursory look at the anti-corruption fight of the present administration and of past administrations in Nigeria will show that the focus has been on individuals who are involved in corruption to the exclusion of the corporations involved.  Yet, as stated earlier, it is almost impossible where large amount of money is involved for corrupt acts like bribery to be done without involving companies. However, most times the companies are not prosecuted or at best prosecuted for other offences. Thus, the question is whether there are limitations or defects in Nigeria’s anti-corruption legislation or whether the lack of or inadequate prosecution of companies for charges of corruption is as a result of some other factors. Therefore, this paper examines the Nigerian legal framework on corruption with a view to identifying limitations if any to an effective anti- corruption fight. The paper argues that there is the need for reforms of the Nigerian anti-corruption legislation in order for the country’s anti –corruption war to be effective.